Factors Related to Drug Overdose Deaths in Ohio - Samuel Borgemenke (Ohio Journal of Public Health, 2023)
Background: Drug overdoses have had a devastating impact on public health in Ohio. Improving our understand-ing of the relationships between factors that are associated with drug overdose deaths can enhance the quality of public policy and health care reach in Ohio. Methods: Utilizing data from the Centers for Disease Control and Prevention (CDC) and University of Wisconsin Population Health Institute, this research seeks to quantify the associations between the drug overdose rate for counties in Ohio with various factors via statistical regressions. Results: The overwhelming majority of drug/alcohol overdose deaths during the years 2017-2019 were uninten-tional. Drug overdose deaths and life expectancy are strongly associated. Communities with higher overdose rates have lower life expectancies. Socioeconomic status and health care factors, such as mental distress and physical inactivity, are significantly correlated with increased drug overdose deaths. Household income is significantly correlated with increased access to health care, implying that communities of lower socioeconomic status may lack adequate access to quality care and suffer from increased overdose deaths. Conclusion: The data indicate the importance of access to health care and health care providers in response to drug overdoses in Ohio. Health care access is currently proportional to income; higher income households have a greater proportion of insured, as well as a greater number of primary care physicians. Thus, implementing policies that support health care infrastructure should be prioritized to increase the capacity of treatment in under-resourced (low-income and low socioeconomic status) communities.
Keywords: Regression; Drug overdose; Health care; Social determinants; Opioids